Stylistic classical Chinese poem generation - the anatomy of an AI poet - Geng, Runqiu (Nanyang Technological University, 2023)
Traditional poetry, as a cultural treasure, has had a profound impact on every generation throughout human history. Poetry is a way to express emotions, but many modern people struggle to write poetry because they don't understand the format. This project consists of three parts and is dedicated to build an AI poem generator that can generate stylistic classical Chinese poems based on user input keywords. Firstly, this project will build a Chinese poetry generator using the sequence-to-sequence model. Then, the project will explore unsupervised and supervised machine learning algorithms to classify Chinese poems by style. Finally, this project will integrate the results of the first two parts and use stylized data to train the Chinese poetry generator. The result is a successful model that generates Chinese poems based on the keywords entered by the user and the style chosen. Through this final year project, the author learnt and practiced many coding skills and knowledge related to natural language processing, as well as enhancing her information gathering and self-learning skills. In addition, through this year-long project, the author has enhanced her project management skills by setting and completing a plan.